ANALISIS BIAYA BAURAN PROMOSI TERHADAP PENDAPATAN KAMAR DI GRAND MIRAGE RESORT & THALASSO BALI - trisna; Ida Ayu Trisna Wijayanthi; Ida Bagus Amerta Kusuma (Warmadewa Management and Business Journal (WMBJ), 2021)
Promotion is a strategy used to introduce products or services that are owned in order to increase room revenue in hotels. Grand Mirage Resort & Thalasso Bali carries out promotional activities by means of advertising, personal selling and sales promotion. However, in reality the cost of the promotional mix and room income do not go hand in hand, so the main point of this research is how the effect of the promotional mix costs on room income at Grand Mirage Resort & Thalasso Bali and the purpose of this study is to find out how the effect of the promotional mix costs in the form of advertising costs, personal costs selling and sales promotion costs to room revenue at Grand Mirage Resort & Thalasso Bali. The data analysis technique used in this research uses descriptive quantitative analysis techniques through classical assumption analysis methods, multiple regression analysis, t test, f test and the coefficient of determination. The results of the t test indicate that partially the advertising cost variable has a significant effect on room income. Based on the F test, advertising costs, personal selling costs, and sales promotion costs simultaneously have a significant effect on room revenue. Based on the results of the analysis, the variable advertising costs, personal selling costs, and sales promotion costs, the advertising cost variable that has the most dominant influence on room income at Grand Mirage Resort & Thalasso Bali.